Extract from the diary of an imprisoned conscientious objector, 1916 (1916)
1916 1914-1918 "Extract from the diary of an imprisoned conscientious objector, 1916" [T0244.jpg], 1916 Extract from Report 28, dated 21 July 1916, issued by the No Conscription Fellowship (NCF) showing the diary of an imprisoned conscientious objector during the First World War.